Induction of the tetracycline repressor: Characterization by molecular-dynamics simulations - Haberl, Florian; Lanig, Harald; Clark, Timothy (Proteins-Structure Function and Bioinformatics, 2009)
Extensive molecular-dynamics simulations show that the distance between the centers of gravity of the two equivalent helices 3 in the DNA-binding heads of the dimer of the tetracycline-repressor protein (TetR) cairn be used as a retiable diagnostic of induction. This is not, however, true for X-ray structures, but only for molecular-dynamics simulations. This is suggested to be because TetR is inherently flexible along the coordinate of the allosteric change (as is always likely to be the case for allosteric proteins), so that crystal-packing forces can determine the conformation of the protein. However, the time scale of the allosteric rearrangement in the absence of DNA-complexation is found to be of the order of tens of nanoseconds, so hat rearrangement can be observed reproducibly in 100 ns simulations. Metastable (pie-equilibrium) conformations of TetR have been observed for up to 60 ns. The likely equilibrium processes and key features of the TetR system are discussed. Proteins 2009; 77:857-866. (C) 2009 Wiley-Liss, Inc.
Keywords: molecular dynamics; signal transduction; tetracycline repressor